Sustained remission in multiple sclerosis after hematopoietic stem cell transplantation. (5th August 2019) - Tolf, Andreas; Fagius, Jan; Carlson, Kristina; Åkerfeldt, Torbjörn; Granberg, Tobias; Larsson, Elna‐Marie; Burman, Joachim
Abstract : Objectives: To determine whether treatment with autologous hematopoietic stem cell transplantation (HSCT) can induce sustained complete remission in patients with multiple sclerosis (MS). Material and methods: Case series of patients with relapsing‐remitting MS (n = 10) treated at a single center between 2004 and 2007 and followed up for 10 years. The patients were treated with a BEAM/ATG conditioning regimen (n = 9) or a cyclophosphamide/ATG conditioning regimen (n = 1) followed by infusion of unmanipulated autologous hematopoietic stem cells. The primary endpoint was sustained complete remission. Sustained complete remission was defined as "no evidence of disease activity‐4, " sustained for a period of at least 5 years without any ongoing disease‐modifying treatment. Furthermore, MS was considered as "resolved" if intrathecal IgG production and cerebrospinal fluid neurofilament light levels were normalized as well. Results: Five out of 10 patients were in sustained complete remission at the end of the study. In three of them, MS was resolved. Conclusions: Our data demonstrate that sustained complete remission after autologous HSCT for MS is possible.